CPC-067 Impact of a Multidisciplinary Team on the Proper Use of Carbapenems: Before/After Survey at Tenon Hospital. (12th March 2013) - Thibault, J; Cordel, H; Vimont, S; Verdet, C; Denis, M; Pialoux, G; Arlet, G; Debrix, I; Guessant, S
Abstract : Background: The optimization of antibiotic therapy has become a major issue. Indeed, the evolution of bacterial resistance requires prescribers to reserve use of antibiotics and especially carbapenems. Various bodies have made recommendations to improve antibiotic regimens and thus preserve the effectiveness of these major antibiotics. At Tenon Hospital, a multidisciplinary unit was created in May 2011. It includes clinicians, bacteriologists, hygienists and pharmacists. Meropenem and ertapenem were already controlled whereas imipenem and doripenem were given without restrictions before May 2011. Purpose: To assess the impact of this new organisation, a study compared the requirements for carbapenems before and after the antibiotic management team was created. Materials and Methods: All patients who received at least one dose of carbapenem were included. Bacteriological and biological characteristics of each patient were found. The compliance of each prescription with the available guidelines was assessed studying the duration of treatment, dose and indications. Two periods were defined: the first between January 2009 and September 2010 and the second between June 2011 and May 2012. Results: Duration of the treatment was the single criteria that had changed for ertapenem and meropenem. The impact of this team is greater for the prescriptions of doripenem and imipenem. Establishment of that team shortened the duration of treatment: 2 days for doripenem and 4 days for imipenem. The number of unjustified prescriptions of imipenem decreased from 45% to 5% for empirical treatments and from 51% to 20% for documented treatments. Conclusions: Reduced length of treatment is important and reduces the selection pressure. This explains why carbapenem-resistant bacteria have been isolated only four times in the past year. Results obtained are similar to those obtained in two Parisian hospitals. No conflict of interest.